METHODS OF SYNTHESIS AND FEATURES OF USING SYSTEMS BASED ON MORIN-METAL COMPLEXES IN FLUORESCENT ANALYSIS METHODS - Asieieva, Dasha (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2021)
The review describes modern physicochemical systems based on complex compounds with organic ligands, which may have fluorescent properties when interacting with metal ions or proteins. Modern methods of synthesis of these compounds and their use in physical-chemical methods of analysis are given. Approaches to detecting the content of metals and proteins using the fluorescent properties of morin complex compounds are considered. Areas of use of the effects of amplification and quenching of fluorescence for the determination of organic compounds and metal ions, especially in the presence of DNA and RNA of different biological origin are described. The influence of surfactants on the fluorescence intensity of complexes with morin was analyzed separately.